Sociocultural and Digital Communication Challenges in AI Adoption for Classroom Communication: Insights from Nigerian Colleges of Education - Olafare Festus; Ogunrinbokun Bamidele Emmanuel (Language, Technology, and Social Media, 2025)
The integration of Artificial Intelligence (AI) in education offers transformative possibilities, particularly in enhancing classroom communication. However, its adoption remains uneven, especially in developing countries like Nigeria, where sociocultural, linguistic, and infrastructural barriers persist. This study investigates the adoption of AI-mediated communication among academic staff at the Federal College of Education (Technical) Akoka, Nigeria. A mixed-methods approach was employed, combining quantitative survey data from 200 respondents with qualitative insights to explore the extent of adoption, challenges encountered, and sociocultural influences. Results indicate that while 19.2% of respondents extensively use AI tools, a significant portion faces challenges such as inadequate funding (42.3%), limited technical expertise (15.4%), and infrastructural deficiencies (25%). Moreover, sociolinguistic issues, including the mismatch between AI tools and local languages, hinder effective communication. Resistance to change, rooted in traditional teaching norms, further complicates adoption. The study contributes by highlighting the interplay between sociocultural norms and technological resistance, offering a multidisciplinary perspective on AI integration in education. Recommendations include targeted professional development, infrastructure improvements, and the creation of culturally adaptive AI tools. These findings provide a replicable framework for enhancing AI adoption in similar educational contexts globally. Future research should explore longitudinal impacts of AI integration on teaching outcomes and develop policies addressing ethical considerations in AI usage. This study underscores the critical need for inclusive and localized AI solutions to bridge the technological gap in education.